2012
DOI: 10.1093/icvts/ivs344
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous and oral iron administration on perioperative anaemia and transfusion requirements in patients undergoing elective cardiac surgery: a randomized clinical trial

Abstract: The use of intravenous or oral iron supplementation proved ineffective in correcting anaemia after cardiopulmonary bypass and did not reduce blood transfusion requirements. [Current Controlled Trials number: NCT01078818 (oral and intravenous iron in patients postoperative cardiovascular surgery under EC)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 24 publications
2
79
0
3
Order By: Relevance
“…The proportion of anaemic patients was significantly lower in the iron isomaltoside 1000 group compared to the placebo group at week 4 (92% of the placebo group patients were anaemic vs. 61·5% in the iron isomaltoside 1000 group). In the study by Garrido‐Martin and colleagues, they concluded that the use of IV or oral iron supplementation proved ineffective in correcting anaemia after cardiopulmonary bypass and did not reduce blood transfusion requirements . One possible reason for this finding is that the patient might have received a lower dose of IV iron compared to our study.…”
Section: Discussionmentioning
confidence: 48%
“…The proportion of anaemic patients was significantly lower in the iron isomaltoside 1000 group compared to the placebo group at week 4 (92% of the placebo group patients were anaemic vs. 61·5% in the iron isomaltoside 1000 group). In the study by Garrido‐Martin and colleagues, they concluded that the use of IV or oral iron supplementation proved ineffective in correcting anaemia after cardiopulmonary bypass and did not reduce blood transfusion requirements . One possible reason for this finding is that the patient might have received a lower dose of IV iron compared to our study.…”
Section: Discussionmentioning
confidence: 48%
“…90 In another study, investigators randomly assigned 159 patients undergoing cardiac surgery requiring cardiopulmonary bypass, in a double-blinded manner, to one of three treatment groups. 91 Group I received 300 mg of intravenous iron(III) hydroxide sucrose complex per 24 h and one placebo tablet per 24 h during preoperative and postoperative hospitalization, with placebo only for 30 days after discharge. Group II received a placebo infusion while hospitalized, and one tablet of oral ferrous fumarate iron per day during hospitalization and for 30 days after discharge.…”
Section: Iron In Nontransplant Cardiac Surgerymentioning
confidence: 99%
“…Physical mobility and well-being were not recorded. 91 On the basis of these studies, no clear recommendation can be given with regard to the correction of iron deficiency in patients undergoing cardic surgery.…”
Section: Iron In Nontransplant Cardiac Surgerymentioning
confidence: 99%
“…Only in subgroups of patients with surgery for intracapsular fractures or with preoperative Hb > 12 g/dl, post-hoc analysis showed significant reductions in RBC transfusion requirements in the IS arm (14 vs 46% [p < 0.005] and 19 vs 35% [p < 0.05], respectively). The last trial was a double-blind study performed in 159 patients undergoing cardiopulmonary bypass surgery [75]. Group 1 received i.v.…”
Section: Perioperative Iron Treatmentmentioning
confidence: 99%